Accelerated forgetting? An evaluation on the use of long-term forgetting rates in patients with memory problems - Geurts, Sofie; van der Werf, Sieberen P.; Kessels, Roy P. C. (Frontiers in Psychology, 2015)
The main focus of this review was to evaluate whether long-term forgetting rates (delayed tests days to weeks after initial learning) are a more sensitive measure to detect memory problems in various patient groups than standard delayed recall measures. It has been suggested that accelerated forgetting might be characteristic for epilepsy patients, but little research has been performed within other populations. Here, we identified ten studies in a wide range of brain injured patient groups, whose long-term forgetting patterns were compared to that of healthy controls. Signs of accelerated forgetting were found within two studies. The results of seven studies showed normal forgetting over time for the patient groups. However, most of the studies used only a recognition procedure, after optimizing initial learning. Based on the results, we discuss recommendations for assessing long-term forgetting and the need for future research to truly evaluate the usefulness for clinical practice.